2015
DOI: 10.3389/fpsyg.2015.01745
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Acceptance? Patients with Social Anxiety Disorder Manifest their Social Expectancy in ERPs During Social Feedback Processing

Abstract: Previous studies on social anxiety have demonstrated negative-expectancy bias in social contexts. In this study, we used a paradigm that employed self-relevant positive or negative social feedback, in order to test whether this negative expectancy manifests in event-related potentials (ERPs) during social evaluation among socially anxious individuals. Behavioral data revealed that individuals with social anxiety disorder (SAD) showed more negative expectancy of peer acceptance both in the experiment and in dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 81 publications
(100 reference statements)
2
51
1
Order By: Relevance
“…In contrast, the FRN pattern among low disinhibition participants did not vary as a function of incentive conditions. To our knowledge, this study is among the first ones to report that correct feedback elicits a larger FRN than incorrect feedback in certain groups of people (see also Cao, Gu, Bi, Zhu, & Wu, 2015), although it has long been acknowledged that the FRN amplitude is sensitive to individual difference in personality constructs (Proudfit, 2015; San Martín, 2012). According to the PRO model, this surprising finding indicates that in the neutral incentive condition, correct outcomes were more unexpected than incorrect ones for high disinhibition participants.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, the FRN pattern among low disinhibition participants did not vary as a function of incentive conditions. To our knowledge, this study is among the first ones to report that correct feedback elicits a larger FRN than incorrect feedback in certain groups of people (see also Cao, Gu, Bi, Zhu, & Wu, 2015), although it has long been acknowledged that the FRN amplitude is sensitive to individual difference in personality constructs (Proudfit, 2015; San Martín, 2012). According to the PRO model, this surprising finding indicates that in the neutral incentive condition, correct outcomes were more unexpected than incorrect ones for high disinhibition participants.…”
Section: Discussionmentioning
confidence: 82%
“…Larger P300 amplitudes were expected after positive compared to negative, and after social compared to non-social feedback. For P2 amplitudes, we hypothesized sensitivity to feedback valence and social dimension (Cao, Gu, Bi, Zhu, & Wu, 2015;Cuthbert et al, 2000;Rigoni, Polezzi, Rumiati, Guarino, & Sartori, 2010). We expected larger amplitudes for social than non-social stimuli; we were not able to state a directional hypothesis for valence effects due to inconsistent previous results.…”
Section: Introductionmentioning
confidence: 68%
“…Cao, Gu, Bi, Zhu, and Wu (2015) found that patients with SAD displayed an increased FRN in response to acceptance feedback from peers. This was interpreted to reflect a violation of negative feedback expectancies, since socially anxious participants anticipated a larger proportion of negative peer feedback in this study (Cao et al, 2015). A difficulty with this interpretation is that expectancies were not recorded during the EEG experiment (on a trial-to-trial basis), but as an overall Likert-scale measure prior to the task to index general expectancies about the social evaluative outcome.…”
Section: Frnmentioning
confidence: 96%
“…However, recent studies showed that depending on the likelihood of an outcome, the FRN component might be sensitive to both negative and positive information (Ferdinand, Mecklinger, Kray, & Gehring, 2012;Oliveira, McDonald, & Goodman, 2007). Cao, Gu, Bi, Zhu, and Wu (2015) found that patients with SAD displayed an increased FRN in response to acceptance feedback from peers. This was interpreted to reflect a violation of negative feedback expectancies, since socially anxious participants anticipated a larger proportion of negative peer feedback in this study (Cao et al, 2015).…”
Section: Frnmentioning
confidence: 99%
See 1 more Smart Citation